ONBUSINESS E-COMMERCE IN MALAYSIA: AN INVESTIGATION OF KEY ADOPTION - Igau, Oswald Aisat; Mohd Kassim, Abdul Wahid; Hamidi, Masyhuri; Sidin, Julian Paul; Tahajuddin, Sulaiman; Ayub, Mat Salleh (JURNAL BISNIS STRATEGI, 2008)
Non-business EC is a relatively new research niche In the general e-commerce stream. It denotes the use of e-commerce by non-business institutions such as academic institutions (as in the present study), not- for profit organizations, religious organizations, and government agencies to reduce their expenses or to improve their operations and customer service. A field survey was conducted to determine key factors that facilitate the adoption of non-business EC In Malaysian Universities. Since e-commerce adoption decision is a strategic one, a comprehensive list of potential facilitators and non-facilitators for the strategic use of information technology was derived from past research and used as the basis for collecting data from 65 schools, centres and units from 5 public universities in Kota Kinabalu and Kuala Lumpur. These data were factor-analysed to determine the key underlying dimensions of facilitators. On the basis of the resulting five dimensions namely, relative advantage, network orientation, Information efficiency, innovativeness, and competitiveness, regression analysis was done to determine the impact of the five dimensions on adoption. Non-business EC was parted Into two: (1) partial EC (or a-brochure) where adoption Is solely for promotion and dissemination of product or service information, (2) full EC, which Includes the use of the application for ordering or reserving service, payment, and off-line or on line delivery. The results suggest that relative advantage, network orientation, and Information efficiency are the most lmportant facilitators. Inhibitors were not estimated eventually, as there were no non-users among the respondents. In other words all the respondents are at least adopters of partial EC. Full Implications of the findings are discussed.